Functional Imaging with 18F-FDG PET/CT and Diffusion Weighted Imaging (DWI) in Early Response Evaluation of Combination Therapy of Elotuzumab, Lenalidomide, and Dexamethasone in a Relapsed Multiple Myeloma Patient - Christos Sachpekidis; Antonia Dimitrakopoulou-Strauss; Stefan Delorme; Hartmut Goldschmidt (Diagnostics, 2017)
Elotuzumab is the first monoclonal antibody approved for the treatment of relapsed-refractory multiple myeloma (MM) in combination with lenalidomide, an immunodulatory drug, and dexamethasone. We report on a multiply pre-treated MM patient with disease progression due to appearance of new focal lesions on imaging modalities, who was started on a combination treatment of elotuzumab, lenalidomide, and dexamethasone. After completion of three cycles of the new therapy the patient responded very well with a major decline of serological myeloma activity parameters serum monoclonal protein, kappa light chains, free light chains (FLC) ratio. The patient was also monitored with the functional imaging modalities 18F-FDG PET/CT and diffusion weighted imaging (DWI), which exhibited a mismatch of almost complete metabolic remission on positron emission tomography/computed tomography (PET/CT) with 18F-fluoro-2-deoxy-d-glucose (18F-FDG) (consistent with the serological response), and signal elevation persistence on DWI. This case demonstrates the potentially superior performance of 18F-FDG PET/CT over DWI in early response evaluation of combined treatment with a monoclonal antibody, an immunomodulatory drug, and dexamethasone in MM.